Pengaruh Disiplin Kerja, Motivasi, Kompensasi dan Lingkungan Kerja Terhadap Produktivitas Kerja Karyawan Pada PT. Kresna Karya Basecamp Akah Klungkung - Trisnayani, Ni Komang; Irwansyah, M. Rudi (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the effect of work discipline variables, motivation, compensation, and work environment on employee productivity at PT Kresna Karya Basecamp Akah Klungkung. The population in this study were employees of PT Kresna Karya Basecamp Akah Klungkung. The number of samples used in this study was 45 respondents. The sampling technique in this study was simple random sampling technique using the Slovin formula. The data in the study were collected by distributing questionnaires. Data processing in this study was done using the help of the Statistical Package for the Social Sciences (SPSS) program version 25. The analysis technique used is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this study indicate that (1) work discipline affects employee work productivity, (2) motivation affects employee work productivity, (3) compensation affects employee work productivity, (4) the work environment affects employee work productivity, and (5) work discipline, motivation, compensation, and the work environment simultaneously affect employee work productivity at PT Kresna Karya Basecamp Akah Klungkung.